MANAGEMENT OF INCOMPLETE CERVICAL DILATATION DURING ABORTION IN A COW - DEWRY, R K; ISLAM, K; TALUKDAR, D J; DEORI, S; SAIKIA, B; HAZARIKA, S B (The Indian Journal of Animal Reproduction, 2023)
A case of incomplete cervical dilatation in a crossbred cow during abortion and its successfulmanagement is reported.
Keywords: Abortion; Cow; Incomplete dilatation of cervix